Cases and materials in company law - Sealy, Len (Oxford University Press, 2004)
The seventh edition of Cases and Materials in Company Law has been enlarged to include the Law Commission's recommendations for company law reform and the DTI's ongoing Company Law Review project. All contents have been updated to include the effect of the Human Rights Act 1998 and to cover vital cases including the Centros decision, the House of Lords' judgment in O'Neil v Phillips and the Privy Council ruling in the Brumark case. Covering a wide range of sources, Cases and Materials in Company Law is essential reading for all those who need access to important matierals in one place